Rites for the Dead, Amity for the Living: the Old Assyrian nasbītum Rite and Its Relation to the Old Babylonian kispum - Nation, Trey (2024)
While recent scholarship has clarified the spelling of the little-known Old Assyrian nasbītum rite, formerly glossed as naspittum, its etymology and social context have remained obscure. This paper suggests the elusive rite has its etymology in the OA verb sabā’um, “to brew/draw beer,” and refers to the act of libation. While the textual evidence for nasbītum is currently limited, an analysis of the rite as it occurs in the OA corpus suggests that nasbītum was the OA term for the care and feeding of the spirits of the dead, analogous to the better-known Old Babylonian kispum.
Keywords: naspittum; nasbītum; Libation; ancestor cults; Old Assyrian religion; Kispum; Ritual